Cultural Distance, Firm Boundaries, and Global Sourcing - Yuriy Gorodnichenko; Bohdan Kukharskyy; Gerard Roland (Center for Economic Studies and ifo Institute (CESifo), 2023)
Casual observation suggests that cultural differences play an important role in business transactions, yet systematic evidence on this relationship is scarce. This paper provides a novel investigation of the effect of cultural distance on multinational firms' decisions to integrate their cooperation partners into firm boundaries, rather than transact with independent companies at arm's-length. To guide our empirical analysis, we develop a simple theoretical model which suggests that (i) cultural distance between contracting parties decreases the relative attractiveness of integration, and (ii) this effect is mitigated in more productive firms. We test these predictions using extensive product-, industry-, and firm-level data. We find a robust negative relationship between cultural distance and the relative attractiveness of integration. In line with our theoretical predictions, we also find that the effect of cultural distance on firm boundaries is less pronounced the higher firm's productivity.
Keywords: F14; F23; L14; L23; 330; cultural distance; firm boundaries; international make-or-buy decision; firm productivity